2016
DOI: 10.1371/journal.pntd.0004468
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Human Visceral Leishmaniasis Restores Antigen-Specific IFN-γ, but not IL-10 Production

Abstract: One of the key immunological characteristics of active visceral leishmaniasis (VL) is a profound immunosuppression and impaired production of Interferon-γ (IFN-γ). However, recent studies from Bihar in India showed using a whole blood assay, that whole blood cells have maintained the capacity to produce IFN-γ. Here we tested the hypothesis that a population of low-density granulocytes (LDG) might contribute to T cell responses hyporesponsiveness via the release of arginase. Our results show that this populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 31 publications
6
43
1
Order By: Relevance
“…These results show that despite the “clinical cure,” the immune system of these patients is still impaired at the time they are released from hospital. This is in line with our previous study that showed that the capacity of whole blood cells to respond to antigenic and polyclonal stimulation with IFN-γ production was not restored in treated patients (7). This is of relevance in Ethiopia, where a new treatment is used, a combination of PM and SSG, which reduced the hospitalization of VL patients from 28 to 17 days.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results show that despite the “clinical cure,” the immune system of these patients is still impaired at the time they are released from hospital. This is in line with our previous study that showed that the capacity of whole blood cells to respond to antigenic and polyclonal stimulation with IFN-γ production was not restored in treated patients (7). This is of relevance in Ethiopia, where a new treatment is used, a combination of PM and SSG, which reduced the hospitalization of VL patients from 28 to 17 days.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, this notion was challenged by studies performed in India (5, 6): using a whole blood assay, the authors showed that CD4 + T cells produce similar levels of IFN-γ that can limit Leishmania parasite replication during active VL. In contrast, our recent work performed in Ethiopia showed that whole blood cells produce no or low IFN-γ, suggesting that whole blood cells from VL patients in Ethiopia are hyporesponsive (7). …”
Section: Introductionmentioning
confidence: 77%
“…The latter reported on an incremental increase in IFN-γ levels in cured individuals living in Northwest Ethiopia as compared to active patients but could not detect differences in IL-10 levels. Similar findings were reported in Turkish, Indian, Iranian, Spanish, and Bangladeshi VL patients [20,21,23,32,33], indicating a typical cellular hyporesponsiveness during active disease that restores after successful therapy, as was also reported in studies using peripheral blood mononuclear cell (PBMC). This was also reflected in the gradual increase in nonspecific PHA stimulation which suggests a broad mechanism of immunosuppression that merits further investigation.…”
Section: Discussionsupporting
confidence: 85%
“…This was also reflected in the gradual increase in nonspecific PHA stimulation which suggests a broad mechanism of immunosuppression that merits further investigation. Studies in Spain and Ethiopia demonstrated that a long-lasting memory response remains in cured patients and increased levels of IFN-γ and IFN-γ-inducible protein 10 (IP-10) could be detected in almost all patients at 6 and 12 months after treatment [21,23]. This is, however, the first time that a longitudinal study in diseased individuals was performed with an early measurement at one week of treatment.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation